Filsafat Wasiat Wajibah dalam Sistem Hukum Kewarisan Islam di Indonesia - Titing Oting Supartini; Aden Rosadi; Usep Saepullah; Husain Husain (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the philosophy of wasiat wajibah (obligatory bequest) within the Islamic inheritance law system in Indonesia, by examining its philosophical, normative, and practical foundations in the context of national law. Wasiat wajibah is a legal institution that grants a mandatory inheritance share to heirs who are otherwise excluded from inheritance rights, such as grandchildren whose parent (the child of the deceased) has passed away before the testator. The purpose of this study is to examine the philosophical foundations of wasiat wajibah, its relevance to the Islamic principle of justice, and its integration into Indonesia's positive legal system. This research adopts a qualitative approach with a normative-philosophical method. Data were collected through literature review of both primary and secondary sources, including classical Islamic jurisprudence texts, Indonesian legal regulations (such as the Compilation of Islamic Law), and philosophical writings on Islamic legal thought. The data were analyzed interpretively and reflectively through textual and conceptual analysis. The findings indicate that wasiat wajibah is grounded in strong philosophical principles of justice, compassion, and protection of vulnerable groups. In the Indonesian context, this concept has been incorporated into the Compilation of Islamic Law, particularly in Article 209, as a form of legal adaptation to the complex and plural realities of modern society. However, its implementation still faces challenges due to differing scholarly opinions among Islamic schools of thought and limited awareness among legal practitioners. In conclusion, wasiat wajibah serves as a bridge between Islamic moral values and a responsive positive legal system. A philosophical approach to wasiat wajibah reinforces the urgency of reconstructing the Islamic inheritance system in Indonesia to be more just, adaptive, and contextually relevant.